Linear and nonlinear optics : materials, properties, and applications - Locharoenrat, Kitsakorn (Singapore : Jenny Stanford Publishing, 2021)
In recent years, optical properties of the unique atomic and molecular structures of materials have drawn great scientific interest. Linear optical properties of materials such as metals, metal oxides, magnetic oxides, and organic materials are based on energy transfer and find applications in wastewater treatment, forensic science, biomedical science, photovoltaics, nuclear technology, and LED displays. Nonlinear optical properties of materials are based on the nonlinear medium and find more advanced applications in frequency mixing generations and optical parametric oscillations. This book presents the underlying principles, implementation, and applications of the linear and nonlinear optical properties of materials and has been divided into two parts emphasizing these properties. The first part of the book, Linear Optics, discusses bimetallic nanoparticles in dielectric media and their integration to dye molecules to detect trace amounts of heavy metals at the nanometer level, as well as to enhance luminescence and image contrasts in forensic inspection and biomedical diagnosis. It shows how the integration of bimetallic nanoparticles into a ZnO matrix promotes broadening of the absorption spectrum from the ultraviolet to the visible wavelength. It explains the role of surface adsorption and photocatalytic degradation in dye-removal kinetics by Fe3O4 magnetic nanoparticles under pulsed white light. It also discusses the double-layer shielding tank design to safely store radioactive waste and photon propagation through the multilayer structures of a human tissue model. The second part of the book, Nonlinear Optics, presents general concepts such as electromagnetic theory, nonlinear medium, and wave propagation, as well as more advanced concepts such as second harmonic generation, phase matching, optical parametric interactions, different frequency generation, sum frequency generation, tunable laser, and optical resonant oscillator.
OCLC-licensed vendor bibliographic record.
Keywords: Nonlinear optics -- Materials; Materials -- Optical properties; SCIENCE / Nanostructures; SCIENCE / Optics; SCIENCE / Spectroscopy & Spectrum Analysis